2021
DOI: 10.1007/s13202-020-01081-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and analysis of naturally fractured gas reservoirs based on stimulated reservoir volume and petro-physical parameters

Abstract: Fracture is one of the most important geological phenomena that affect the production of hydrocarbon compounds in broken carbonate reservoirs. However, fracture controlling factors must be combined with well data to achieve accurate fracture modeling. Therefore, structural data, drilling data, well flow diagrams, cores data, wells production data, and dynamic reservoir data have been considered here. Finally, by combining the above-mentioned information and through statistical and mathematical methods, the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…28−32 Hence, this requires innovative technologies to enhance the productivity of shale gas reservoirs. 33,34 Such techniques include carbon dioxide (CO 2 ) injection, 35−37 acidizing, 38 hydrofracking, 39−41 drilling optimization, [25][26][27]42 and liquid nitrogen (LN 2 ) fracturing (a recently developed technique). 13,15,18,30,31,43,44 The fracturing mechanisms of shale gas reservoirs are unlike those of conventional reservoirs (sandstones).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28−32 Hence, this requires innovative technologies to enhance the productivity of shale gas reservoirs. 33,34 Such techniques include carbon dioxide (CO 2 ) injection, 35−37 acidizing, 38 hydrofracking, 39−41 drilling optimization, [25][26][27]42 and liquid nitrogen (LN 2 ) fracturing (a recently developed technique). 13,15,18,30,31,43,44 The fracturing mechanisms of shale gas reservoirs are unlike those of conventional reservoirs (sandstones).…”
Section: Introductionmentioning
confidence: 99%
“…The conventional methods of exploitation and development of such resources have limited applicability in their extraction. ,,,, Additionally, the economical production from such reservoirs cannot be achieved by conventional means due to their complex pore system and lesser connectivity, complex pore geometry, extremely low porosity, and permeability. Hence, this requires innovative technologies to enhance the productivity of shale gas reservoirs. , Such techniques include carbon dioxide (CO 2 ) injection, acidizing, hydrofracking, drilling optimization, , and liquid nitrogen (LN 2 ) fracturing (a recently developed technique). ,,,,,, …”
Section: Introductionmentioning
confidence: 99%
“…Fracture permeability is mostly much greater than the rock matrix's permeability, particularly in carbonates, that is because the ability of fluid to flow in naturally fractured reservoirs is inclined to be governed by the fracture network (Guerriero et al 2013;Carey et al 2020;Lv et al 2021;Ceccato et al 2021). It is the fundamental characteristics of fractures and expansive fracture networks that control the flow of hydrocarbons in naturally fractured reservoirs (Al-Rubaye et al 2021;Tiab and Donaldson 2015;Voorn et al 2015;Guerriero et al 2013;Afşar et al 2014;Zambrano et al 2021). Consequently, it is important that these characteristics are well defined, and their impacts on fluid dynamics thoroughly understood as early as possible during field development for optimal reservoir flow performance and resource recovery to be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, nanotechnology, in particular nanoparticles (NPs), has received increased attention in the oil and gas industry. This includes Chemical EOR (CEOR) application, which are widely used to produce more oil from unconventional oil reservoirs or once water flooding produce no more oil economically. NPs have recently been suggested as CEOR agents that can be used as dispersion in water or in combination with other chemicals such as brine, CO 2 , surfactants, polymers, or surfactant–polymer solutions. In real reservoir situations, the presence of organic acids is the main factor, which changes the wettability of typical reservoir formation to oil-wet, which may have a significant impact on CO 2 trapping capacities (note that CO 2 injection into typical formation may also have a substantial impact on wettability and asphaltene precipitation). , Recent studies have also shown that NPs can be used as a reversing agent for CO 2 -wet surfaces to hydrophilic surfaces for its implications on CO 2 -geological storage. The type and properties of chemicals formulated with NPs usually depend on the type and condition of the targeted oil reservoirs and the specific application. , For instance, polymer flooding, a classic chemical EOR (CEOR) technique, was originally suggested to be a practical alternative for water flooding in unconventional reservoirs that contain heavy (viscous) crude oils. , However, certain reservoir conditions, such as high salinity, increased temperature, or various heterogeneity, can dramatically reduce the feasibility of polymer flooding. Limitations such as chemical degradation and polymer solution instability can drastically affect the efficiency of the polymer as an EOR agent. , Synthetic fluids that use nanosized materials, internal breakers, and low molecular weight surface active materials can be used to achieve the performance of cross-linked polymer fluids and overcome the limitations of the polymer…”
Section: Introductionmentioning
confidence: 99%